Autoimmune liver disease triggered by SARS-CoV-2: a case report and review of the literature - Fanni, D; Gerosa, C; Serra, G; Miglianti, M; Coghe, F; Van Eyken, P; Faa, G; La Nasa, G; Guido, M (European review for medical and pharmacological sciences, 2024)
An increasing number of coronavirus disease 2019 (COVID-19) related autoimmune hepatitis (AIH) and autoimmune liver disease (AILD) has been already described so far in the last three years. This rise has set up some diagnostic and therapeutic concerns, although steroid therapy has mostly been efficient, avoiding main significant side effects. We report the case of a 52-year-old subject displaying liver function impairment at the laboratory tests while positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) swab. Needle liver biopsy showed severe portal inflammation, interface hepatitis, lobular inflammation, abundant plasma cells, bridging necrosis, endothelialitis, bile duct vanishing disease, and ductular reaction. The diagnosis of autoimmune liver disease (AILD) was performed. After a month of steroid and ursodeoxycholic acid medications, liver function fully recovered. Azathioprine was introduced, and steroids were gradually reduced. Probably triggered by the SARS-CoV-2-induced cytokine storm, the association between COVID-19 and autoimmune-related inflammatory injury may display a particular paradigm of AILD pathogenesis.